2012
DOI: 10.1103/physrevb.85.235129
|View full text |Cite
|
Sign up to set email alerts
|

Constraint density functional calculations for multiplets in a ligand-field applied to Fe-phthalocyanine

Abstract: Multiplets in a ligand-field are treated within total-energy density functional calculations by imposing density matrix constraints on the d-orbital occupation numbers consistent with the local site and state symmetries. We demonstrate the utility of this approach for the case of isolated Fe phthalocyanine (FePc) molecules with overall D 4h symmetry: We find three stationary states of 3 Eg, 3 A2g, and 3 B2g symmetries of the Fe 2+ ion and total energy calculations clearly demonstrate that the ground state is 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
46
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 31 publications
13
46
4
Order By: Relevance
“…Ignoring the antibonding orbital of x 2 − y 2 symmetry lying at too high energy [5], out of the four remaining states one can construct four spin-triplets:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ignoring the antibonding orbital of x 2 − y 2 symmetry lying at too high energy [5], out of the four remaining states one can construct four spin-triplets:…”
mentioning
confidence: 99%
“…constrained DFT) [5]. Measurements of the x-ray magnetic dichroism (XMCD) at Fe-L 23 absorption edge showed a large, unquenched orbital moment [3].…”
mentioning
confidence: 99%
“…[16] Marom et al ) or 3 A 2g depending on computational details [17]. Nakamura et al [18] found 3 A 2g for isolated FePc and 3 E g (a) for linear chains. Recently, from multiplet calculations [19,20] the ground state was found to be 3 E g (b).…”
Section: Introductionmentioning
confidence: 99%
“…2,[10][11][12][13][14] For the MnPc, the multiplet for ground state has been suggested either 4 E g or 4 B 2g state, 11,15,16 and for the CoPc, the 2 E g or 2 A 1g state. 11,13 For this, we previously proposed a constraint DFT approach, implemented in the full-potential linearized augmented plane-wave (FLAPW) method, 17 by imposing density matrix constraints on the d-orbitals occupation numbers, and our total energy calculations demonstrate that for the FePc, there are three stationary states of the 3 E g , 3 B 2g , and 3 A 2g symmetries and that the ground state is the 3 A 2g state with a planar magnetic anisotropy (MA). Here, we extend our DFT investigations for the MnPc and CoPc, and we demonstrate that for the MnPc (CoPc), the ground state is the 4 E g ( 2 A 1g ) state with the out-of-plane (planar) MA.…”
Section: Introductionmentioning
confidence: 99%